2003
DOI: 10.1046/j.1365-2141.2003.04419.x
|View full text |Cite
|
Sign up to set email alerts
|

A 2·6 Mb interval on chromosome 6q25.2–q25.3 is commonly deleted in human nasal natural killer/T‐cell lymphoma

Abstract: Summary. Natural killer (NK)/T-cell lymphoma is a special subtype of rare malignant lymphoma that is more prevalent in Asia than in America and Europe. This newly characterized haemato-lymphoid malignancy is highly aggressive and frequently present in nasal and upper aerodigestive sites. Several studies have reported the commonly deleted region of chromosome 6q21-25 in this particular type of lymphoma. To refine the smallest region of overlapping (SRO) deletion for localization of potential tumour suppressor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 41 publications
0
27
0
1
Order By: Relevance
“…7,10,11,21,39 Previous results and our data suggest that 6q21 (B105.6-107 Mb) is the most common aberrant region (Table 1a). Of the eight known genes in the common minimal region of the 6q21 locus, ATG5 and PRDM1 (Blimp-1) had the most consistently low expression.…”
Section: Genomic Studies On Natural Killer-cell Malignancies J Iqbal mentioning
confidence: 94%
“…7,10,11,21,39 Previous results and our data suggest that 6q21 (B105.6-107 Mb) is the most common aberrant region (Table 1a). Of the eight known genes in the common minimal region of the 6q21 locus, ATG5 and PRDM1 (Blimp-1) had the most consistently low expression.…”
Section: Genomic Studies On Natural Killer-cell Malignancies J Iqbal mentioning
confidence: 94%
“…64 Furthermore, 6q-had also been localized to CD3ÀCD56 þ lymphoma cells, 65 confirming that the chromosomal aberration was restricted to neoplastic NK cells. A commonly deleted region in chromosome 6q21 to 6q25 had been defined by fluorescence ISH and molecular genetic methods, 66,67 Comparative genomic hybridization and loss of heterozygosity studies had shown that, in addition to 6q-, deletions in chromosomes 11q, 13q and 17p were also present. 68,69 The putative genes implicated in these deletions have not been identified.…”
Section: Molecular Pathology Of Nk-cell Lymphomasmentioning
confidence: 99%
“…Cependant, un mécanisme de trogocytose 1 a été proposé pour expliquer la présence du récepteur au virus sur ces cellules : lors d'un contact rapproché avec une cellule B activée, les cellules NK peuvent acquérir, par transfert de membrane plasmique, le récepteur CD21 et ainsi être infectées par le virus EBV. La prolifération des cellules NK infectées par l'EBV est ensuite favorisée par la production de nombreuses cytokines (interleukine [ 50 % des cas de lymphomes NK/T [6,9,10,17,[19][20][21][22]. Elle s'associe en particulier à la diminution de l'expression du gène PRDM1 (PR domain containing 1) [9].…”
Section: Anomalies Moléculairesunclassified